Predictors of News Media Use in the COVID-19 Pandemic. A Brief Research Report - Iwanowska, Magdalena; Kondratowicz, Blanka; Zawadzka, Anna Maria (Przegląd Psychologiczny, 2023)
Aim: The research aimed to explore personal goals and COVID-19-related fear & worries as predictors of news media use during a health crisis – the COVID-19 pandemic. Method: A correlational online study was conducted with 371 subjects (Mage = 28.88, SDage = 10.25). Results: The results showed that, as expected, the importance of the health goal and the level of COVID-19 fear & worries positively predicted news media use, and the importance placed on the exciting life goal negatively predicted news media use during the COVID-19 pandemic. There was no significant relationship between the safety goal and news media use. However, the study revealed that COVID-19 fear & worries partially mediated the relationship between the safety goal and news media use. Conclusions: Study confirms that personal goals and negative emotions related to a crisis play an important role in understanding how and why people use the news media in a crisis. The limitations of the study and theoretical and practical implications are discussed.